Effects of Harvest and Storage of Switchgrass on the Recovery of Carbohydrates during Dilute Acid Pretreatment and Enzymatic Hydrolysis. Issue 1 (1st December 2014) - Djioleu, Angele C.; Sverzut, Claudio B.; Martin, Elizabeth M.; Childress, Evan; Johnson, Casey; West, Charles P.; Carrier, Danielle Julie
Abstract : Perennial forage grasses have potential as cellulosic feedstocks. Outside storage as round bales is a likely mode of storage; however, little is known of storage effects. The objective of this study was to determine the effects of baled storage method on saccharification, namely the recovery of glucose and xylose, and production of inhibitors after dilute acid pretreatment and enzymatic hydrolysis. Mature switchgrass ( Panicum virgatum L. cv. Alamo) was harvested in Fayetteville, AR and packaged in large round bales in October 2010. There were two baling times: one soon after cutting when there was no rainfall and the other after a rainfall event. The bales that did not receive rain were stored either in an open barn or unprotected in the field. Bales made from rained‐on switchgrass were only stored unprotected in the field. Samples were taken from the windrows right before baling, and after a maximum 65‐day storage period. Field storage increased lignin content in biomass relative to barn storage, but carbohydrate constituents were not affected. Field storage decreased production of hydroxymethylfurfural and increased production of furfural relative to barn storage. Results indicate that protected storage conditions for switchgrass biomass in round bales can lead to greater preservation of fermentable sugars and reduced production of the important inhibitor furfural.